(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
This paper studies the performance of the National Scholarship Program for Higher Education in Mexico and its influence on the reduction of scholar dropout in that grade level, through review and synthesis of various investigations and also official assessments that the program has been through. The analysis is complemented by an empirical study conducted at the Universidad de Occidente, campus Guasave, through surveys and interviews with grant holders of the program and an interview with the person responsible for it in the campus. Testimonials and empirical data generated in the study are consistent with the criticisms expressed by the experts in the sense of the erosion of purchasing power of the scholarship and the lack of coverage of the program. The biggest criticism of grant holders refers to irregular payments, which prevents properly plan their expenses.